1987
DOI: 10.1136/jcp.40.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Factor II, VII, IX and X concentrations in patients receiving long term warfarin.

Abstract: Material and methods Thirty seven consecutive outpatients who had received warfarin for not less than three months were studied. There were 20 women aged 28-73 years (mean 60 years) and 17 men aged 28-78 years (mean 59 years). Eleven had been receiving warfarin for less than one year, while eight had been treated for longer than 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 5 publications
4
23
1
Order By: Relevance
“…The pattern of procoagulant level reductions found in our therapeutically anticoagulated patients is in accordance with that of other studies [5,6,14]. The absence of a difference in factor II and factor VII in therapeutically anticoagulated patients on acenocoumarol may be explained by the fact that blood was collected 12-18 h after drug intake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pattern of procoagulant level reductions found in our therapeutically anticoagulated patients is in accordance with that of other studies [5,6,14]. The absence of a difference in factor II and factor VII in therapeutically anticoagulated patients on acenocoumarol may be explained by the fact that blood was collected 12-18 h after drug intake.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies has been carried out on the extent to which the different vitamin K-dependent procoagulant factors are depressed in patients on long-term oral anticoagulant therapy at therapeutic levels of anticoagulation [3][4][5][6]: factor X is most strongly reduced, and factor IX is least strongly reduced. However, to our knowledge, there are no reports that focus on the levels of these factors in over-anticoagulated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Also, warfarin therapy does not result in uniform reduction of the vitamin K-dependent factors. 10 These differences are relevant in consideration of the rate of reversal of warfarin and were demonstrated in our study, with the large 95% confidence interval in the time to surgery. Administering vitamin K reverses the anticoagulant effect of warfarin because conversion to the activated form of vitamin K may occur by a warfarin-resistant enzyme pathway.…”
Section: Discussionmentioning
confidence: 86%
“…In a study of 37 patients, Paul et al (1987) found that FX levels were the lowest, FII levels intermediate and FVII and FIX levels the highest. Similar findings were also reported in 50 patients (Lind et al, 1997).…”
Section: Discussionmentioning
confidence: 96%